2014
DOI: 10.9790/2380-07118085
|View full text |Cite
|
Sign up to set email alerts
|

In-vitro Evaluation of Some Selected Fungicides against Pestalotio psis clavispora and Pseudocochliobolus eragrostidis Isolated from Vitellaria paradoxaSeedlings.

Abstract: Preliminary investigation into the nursery diseases of Vitellaria paradoxa in the Nigerian

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The present study showed that captan inhibited 20–80% of the growth of pestalotioid fungi. Similarly, Esiegbuya et al 55 reported the effect of captan at 250 and 500 ppm on the in vitro mycelial growth of P. clavispora; however, the fungicide did not completely inhibit the pathogen .…”
Section: Discussionmentioning
confidence: 93%
“…The present study showed that captan inhibited 20–80% of the growth of pestalotioid fungi. Similarly, Esiegbuya et al 55 reported the effect of captan at 250 and 500 ppm on the in vitro mycelial growth of P. clavispora; however, the fungicide did not completely inhibit the pathogen .…”
Section: Discussionmentioning
confidence: 93%